An Equivalent Medium Method for the Vacuum Assisted Resin Transfer Molding Process Simulation - Dong, Chensong (Sage Publications, 2006)
Computer simulation has been an efficient and cost-effective tool for liquid composite molding, including resin transfer molding (RTM), vacuum assisted resin transfer molding (VARTM), and resin infusion, compared to trial and error. The control volume finite element method (CVFEM) has been the predominant method for simulation. When the CVFEM simulation is used for the VARTM process, because of the existence of two distinct flow media: fiber preform and high permeable media (HPM), 3-D models are required. Since the HPM is usually much thinner than the fiber preform, a large number of nodes and elements need to be used in simulation, which significantly increases the computation load and time. In addition, the time-consuming preprocessing process makes simulation not feasible for industry applications. This article presents an equivalent medium method (EMM) for fast and accurate VARTM process simulation. This method increases the thickness of the HPM or both the HPM and the fiber preform and applies the equivalent material properties. This is an improved method over previously presented equivalent permeability method (EPM) by correcting its two shortcomings: (1) The EPM does not account for the influence of the porosity of HPM, thus the resin flow through HPM is changed and (2) The EPM does not consider the change of through-thickness permeability after the equivalence. A new mesh generation algorithm is also discussed, which provides a faster and more convenient way for preprocessing. The approach presented in this article provides the fundamental for developing a universal computer simulation tool for both the RTM and VARTM processes. The effectiveness of this approach has been validated by comparing to the conventional CVFEM simulation and experiments.